Indonesian Presidential Election 2019 – East Java : Deadheat in a Battleground Province - Arifianto, Alexander Raymond (2019)
Home to roughly 31 million eligible voters, both President Joko Widodo and his opponent Prabowo Subianto are currently locked in a statistical deadheat in East Java – a key province in which the winner is likely to become Indonesia’s next president.